Desain Model Manajemen Pembelajaran Budi Pekerti Berbasis Manajemen Sekolah pada Sekolah Dasar di Kabupaten Purworejo - Nurhidayati Nurhidayati; Titi Anjarini; Joko Purwanto; Lia Yuliana; Nurtanio Agus Purwanto; Arba’atun Nisa; Karisma Nur Fadilah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to construct a hypothetical design of a school-management-based character learning management model for elementary schools in Purworejo Regency. The study employed a Research and Development (R&D) approach; however, this article is limited to the preliminary study, needs analysis, theoretical and philosophical review, and model-design construction. The study was conducted in three elementary schools in Purworejo Regency in April 2026 and involved 3 principals and 32 teachers. Data were collected through interviews, observations, and document analysis, and were analyzed qualitatively through data condensation, data display, and conclusion drawing. The preliminary findings indicate that character values had been incorporated into school visions and missions, school programs, habituation activities, and classroom learning. Nevertheless, their management remained general, was not yet systematically integrated, and was not supported by a management design connecting planning, role distribution, implementation, evaluation, and follow-up. Accordingly, the proposed design integrates school-based management principles with the management functions of planning, organizing, actuating, and controlling (POAC). These managerial processes are directed toward value internalization through ngerti (knowing), ngrasa (feeling), and nglakoni (doing). The design positions principals, teachers, education personnel, parents, and the community as collaborative actors and uses feedback to support continuous improvement. The result of this study is a hypothetical model design and not a final model.